Drilling system design project 1967 final report of drill head committee - Boshier, G. C.; Pike, G. W. H. (College of Aeronautics, 1967)
This report outlines the design of the Drill Head for a numerically controlled drilling machine. The Committee chose to employ a nydraulic main spindle drive. As a result of the problems experienced by Wadkin Limited, Leicester, with hydraulic feed control, it was decided to replace the original hydraulic feed actuator by a conventional 18 speed gearbox. Drill depth control is achieved by conventional gate stops employing pneumatic sensing elements to keep in line with the fluidic elements of the control system. The latter section of the report makes recommendations for future work on the design of feed mechanisms to avoid the use of gearboxes.